Upaya Meningkatkan Kebugaran Jasmani Siswa Kelas V Sekolah Dasar Negeri 2 Bajulan Kecamatan Loceret Kabupaten Nganjuk Tahun Ajaran 2024/2025 - Bima Kukuh Dwi Pamungkas; Mohammad Nur Kholis; Riyan Asrul Unus; Vaza Deefath Az Azka; Dwi Fany Prayoga; Aditya Sukma Ramadhan; Dewi Yuliana (Universitas Nusantara PGRI Kediri, 2024)
Physical education is basically an indispensable part of the overall education system. The purpose of physical education is not only to develop the physical realm, but also to develop aspects of health, physical fitness, critical thinking skills, emotional stability, social skills, reasoning and ethical actions through physical activity and sports. Based on the description above, the author conducted a study entitled Efforts to Improve Physical Fitness through a Play Approach in Physical Education Learning for Grade V Students in PJOK Learning at Elementary School SD Negeri 2 Bajulan, Loceret District, Nganjuk Regency. The research conducted was Classroom Action Research. The test results for November 20, 2024 after learning using the game approach, the results in cycle I for male students increased to 2.15